Transplacental Nutrient Transport Mechanisms of Intrauterine Growth Restriction in Rodent Models and Humans - Winterhager, Elke; Gellhaus, Alexandra (Frontiers in Physiology, 2017)
Although the causes of intrauterine growth restriction (IUGR) have been intensively investigated, important information is still lacking about the role of the placenta as a link from adverse maternal environment to adverse pregnancy outcomes of IUGR and preterm birth. IUGR is associated with an increased risk of cardiovascular, metabolic, and neurological diseases later in life. Determination of the most important pathways that regulate transplacental transport systems is necessary for identifying marker genes as diagnostic tools and for developing drugs that target the molecular pathways. Besides oxygen, the main nutrients required for appropriate fetal development and growth are glucose, amino acids, and fatty acids. Dysfunction in transplacental transport is caused by impairments in both placental morphology and blood flow, as well as by factors such as alterations in the expression of insulin-like growth factors and changes in the mTOR signaling pathway leading to a change in nutrient transport. Animal models are important tools for systematically studying such complex events. Debate centers on whether the rodent placenta is an appropriate tool for investigating the alterations in the human placenta that result in IUGR. This review provides an overview of the alterations in expression and activity of nutrient transporters and alterations in signaling associated with intrauterine growth restriction and compares these findings in rodents and humans. In general, the data obtained by studies of the various types of rodent and human nutrient transporters are similar. However, direct comparison is complicated by the fact that the results of such studies are controversial even within the same species, making the interpretation of the results challenging. This difficulty could be due to the absence of guidelines of the experimental design and, especially in humans, the use of trophoblast cell culture studies instead of clinical trials. Nonetheless, developing new therapy concepts for IUGR will require the use of animal models for gathering robust data about mechanisms leading to IUGR and for testing the effectiveness and safety of the intervention among pregnant women.